THE ROLE OF SPIRITUAL INTELLIGENCE ON ORGANIZATIONAL COMMITMENT OF EMPLOYEES IN THE HIGHER EDUCATION SECTOR OF PESHAWAR PAKISTAN - Irfan Ullah Stanikzai; Muhammad Ibrahim Sekandary; Mr. Sana Ullah (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Spiritual Intelligence is the ability to behave with wisdom and compassion, while maintaining inner and outer peace, regardless of the situation. SQ is central and most fundamental of all intelligence, because it becomes the source of guidance for others, being an integrating intelligence. spiritual intelligence is all about the benefits of spiritual knowledge used to solve different problems and achieve the daily objective.This study was conducted to investigate the relationship between spiritual intelligence and organizational commitment among the administrative staff in the higher education sector of Peshawar Pakistan. The data was collected through self-administrated questionnaires from the population of administrative staff working in the Higher education sector of Peshawar Pakistan. The spiritual intelligence was measured by using a 24-item scale spiritual intelligence self-report inventory (SISR-24) and organizational commitment was measured using 18 item scales. Being a causal nature of the study, the research has employed regression, correlational and descriptive analysis for this study. The Higher education sector needs to use the application of spiritual intelligence to increase the efficiency, effectiveness of employees at the workplace as well enhance the overall performance of the Higher education sector.